Conceptual Change in Science Teaching and Learning: The Role of Pre-Instructional Conceptions - Heller, Andrew (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Conceptual change, defined as learning that requires the revision of prior knowledge and the acquisition of new concepts, is essential for learning in science. Research has often been framed in the context of misconceptions that need to be corrected. Conceptual change is difficult and essential and should be approached intentionally by recognizing that all learners (including students and teachers) bring pre-instructional conceptions to the classroom. A renewed emphasis for conceptual change research on practical classroom implementation of instructional strategies is necessary for science education to improve. This article builds on the theoretical work done by decades of researchers, while focusing on the real classroom research that has been done on intentional conceptual change.